Honey-fried licorice decoction ameliorates atrial fibrillation susceptibility by inhibiting the NOX2–ROS–TGF-β1 pathway - Yu Qin; Yu Qin; Jingyan Wang; Rong Chen; Zhiling Tang; Hao Zhi; Xiang Wu; Xiaodong Chen; Jialei Fu; Xueting Cai; Jianping Shen; Peng Cao; et al. (Frontiers in Pharmacology)
ObjectiveHoney-fried licorice decoction (HFLD), a well-established traditional Chinese medicine, is widely used to treat atrial fibrillation (AF) in China. However, the specific cardioprotective mechanisms of HFLD in treating AF remain unclear. This study aimed to determine the efficacy of HFLD and validate the efficacy and mechanisms of action of HFLD in reducing AF susceptibility.MethodsSerum oxidative stress biomarker levels of healthy controls and patients with paroxysmal AF were detected using enzyme-linked immunosorbent assay kits. The HFLD components were identified using ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. Wistar rats were intraperitoneally injected with isoprenaline (5 mg/kg) for 2 weeks to construct an AF rat model. The effect of HFLD on AF was assessed with the transesophageal atrial pacing technique and histopathological analysis. The expression levels of NOX2-ROS-TGF-β1 signaling pathway related proteins were detected using Western blot and dihydroethidium staining.ResultsOur clinical trial verified that the expression of MDA increased, whereas SOD, CAT and GSH/GSSG ratio decreased in the serum of patients with paroxysmal AF compared with that in individuals with a normal sinus rhythm. Notably, HFLD treatment could reverse these imbalances. In rat experiments, HFLD was found to reduce oxidative stress and extracellular matrix deposition, thereby effectively reducing AF’s induction rate and duration. Western blot analysis indicated that HFLD downregulated the expression of NOX2 and its regulatory proteins, leading to the inhibition of the downstream TGF-β1–SMAD3 signaling pathway.ConclusionHFLD may reduce AF susceptibility by inhibiting the NOX2–ROS–TGF-β1 pathway, potentially providing new perspectives on AF treatment.